Can the development of cooking skills influence nutritional status and diet in healthy adults? A systematic review and meta-analysis protocol - Eva Débora de Oliveira Andrade; Erika Paula Silva Freitas; Daniele de Souza Marinho do Nascimento; Manuela Mika Jomori; Thais Souza Passos; Grasiela Piuvezam; Bruna Leal Lima Maciel (PLoS ONE, 2025)
Cooking skills are defined as the individual knowledge, confidence, and attitude required to perform culinary tasks, which have been studied as a strategy to improve diet and health outcomes. This article describes a systematic review and meta-analysis protocol aiming to assess whether whether intervention-based development of cooking skills improves dietary quality or nutritional status in healthy adults. The protocol follows the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols [PRISMA-P] and has been registered in the International Prospective Register of Systematic Reviews database (PROSPERO: CRD42022385234). Search strategies will be developed based on the combination of descriptors and executed in the PubMed, Embase, Scopus, Web of Science, and SciELO databases. Only intervention studies linking cooking skills to dietary outcomes will be included. Two trained researchers will independently select articles, extract data, and assess the risk of bias. The methodological quality of the studies will be evaluated using the Cochrane Risk Of Bias In Non-randomized Studies – of Interventions [ROBINS-I] and the Cochrane Risk-of-Bias tool for randomized trials (RoB 2). The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) framework will be employed to assess the quality of evidence. Implementing this protocol will result in the development of a systematic review assessing whether the enhancement of cooking skills can influence the nutritional status and diet of healthy adults. Systematizing this knowledge is important to understanding cooking skills not only as a therapeutic tool when pathologies are present but also as a health prevention strategy. Therefore, the systematic review based on this protocol may contribute to the formulation of effective public health policies aimed at improving nutritional status and diets through the development of cooking skills, thus helping prevent adverse health outcomes such as cardiovascular diseases, diabetes, and obesity.